2021
DOI: 10.3390/nu13124201
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Feeding and Iron Status: “The Unbearable Lightness of Being” Infants

Abstract: The complementary feeding (CF) period that takes place between 6 and 24 months of age is of key importance for nutritional and developmental reasons during the transition from exclusively feeding on milk to family meals. In 2021, a multidisciplinary panel of experts from four Italian scientific pediatric societies elaborated a consensus document on CF, focusing in particular on healthy term infants. The aim was to provide healthcare providers with useful guidelines for clinical practice. Complementary feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“… 8 9 10 Thus, expert committees have emphasized the need for the appropriate introduction of iron-fortified complementary foods (CFs) while breastfeeding. 11 12 Moreover, the AAP recommends iron supplementation from 4 months of age, especially for exclusively breastfed infants. 13 …”
Section: Introductionmentioning
confidence: 99%
“… 8 9 10 Thus, expert committees have emphasized the need for the appropriate introduction of iron-fortified complementary foods (CFs) while breastfeeding. 11 12 Moreover, the AAP recommends iron supplementation from 4 months of age, especially for exclusively breastfed infants. 13 …”
Section: Introductionmentioning
confidence: 99%
“…This review found that the highest anemia and ID prevalence were in children under 1 year old, especially from 6 to 12 months. It is recognized in the literature that at this age, during the complementary feeding phase, when foods are introduced to complement milk feeding, there is an increased risk of nutrient deficiencies, especially ID and IDA [ 114 ]. The prevalence of anemia in children under 6 months was found to be 46.1% in one study conducted in three national counties with high poverty levels.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-agricultural diet had been estimated to have been high in iron and meeting infant and toddler nutrient requirements [ 81 ]. Modern diets often deprive children of iron—the trace element functioning as an oxygen binder in hemoglobin within the red blood cell and serving as an essential nutrient for main metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%